Investigation of anti-asthmatic potential of dried fruits of Vitis vinifera L. in animal model of bronchial asthma. Issue 1 (December 2016) - Arora, Poonam; Ansari, S.; Najmi, Abul; Anjum, Varisha; Ahmad, Sayeed
Abstract Background Fruits ofVitis vinifera L., commonly known as grapes, are largely consumed worldwide because of their high nutritional and medicinal benefits. Context and purpose The present study investigated effects ofV. vinifera fruits in ovalbumin-induced animal model of bronchial asthma. Methods Male wistar rats (except group 1) were sensitized with allergen (ovalbumin, 40 mg/rat + aluminum hydroxide, 2 mg/rat). Groups of sensitized animals were treated orally with either vehicle (0.4 mL/kg), standard dexamethasone (2.5 mg/kg) or alcoholic extract ofV. vinifera dried fruits (31 and 42.5 mg/kg) from day 1 to 28 (n  = 6 for all groups). Inflammatory markers including cell counts, cytokines such as interleukin (IL)-4, IL-5, IL-1β, tumor necrosis factor, immunoglobulin E (IgE), leukotrienes and nitrite levels in both blood/serum and bronchoalveolar fluid were analysed. Breathing rate and tidal volume as lung function parameters were examined by spirometer. Lung tissues were studied for histamine content and histopathology. Results Treatment of sensitized animals with dexamethasone or two doses ofV. vinifera fruits extract inhibited recruitment of inflammatory cytokines, IgE, nitrites and circulating cells particularly eosinophils in blood/serum and bronchoalveolar fluid (p  < 0.001, p  < 0.01 andp  < 0.05). Dexamethasone andV. vinifera fruits extract treatment also normalized lung functions and histamine levels compared to ovalbumin-sensitized controls (p  < 0.05 andp  < 0.01). Moreover, both drugs exhibited protection against airway inflammation in lung histology. Conclusion Results of study demonstrate the effectiveness ofV. vinifera fruits in allergic asthma possibly related to its ability to inhibit cellular response and subsequent production of inflammatory cytokines.